The renewable energy transition and “the People”: Exploring the intersections of right-wing populism and the renewable energy transition in Portuguese media discourses - Valquaresma, A.; Batel, S.; Afonso, A. I.; Guerra, R.; Silva, L. (Environmental Communication, 2024)
Local contestation to the deployment of large-scale renewable energy infrastructures has been increasing. Right-wing populism has also been on the rise across the world. This article aims to explore the potential relations between these two socio-political issues, by analyzing Portuguese media discourses on the renewable energy transition and if and how those expose associations with right-wing populist rhetoric. 465 articles published by Portuguese newspapers were analyzed through Thematic Analysis, which revealed three main themes: Portugal at the forefront of the green transition; the dark side of the transition; and, less pervasively, energy justice as crucial for a green transition. These themes and how they are discursively organized resonate with far-right wing populist rhetoric, such as nationalist, anti-elitist and anti-establishment views. This might find echo in rural communities affected by the green energy transition feelings of marginalization.